Awareness and Attitudes on HIV/AIDS Among Married Madhesi Women in Siddharthanagar (Rupandehi Campus Journal, 2025)
This study investigates public perceptions and awareness of HIV/AIDS in Ward No. 9 of Siddharthanagar Municipality, Nepal. Using purposive and systematic sampling, data were collected from 110 respondents via interview schedules and attitude scales. Most participants were semi-literate and held misconceptions about HIV transmission, including beliefs that it spreads through mosquito bites, kissing, or shared food. Married women in particular lacked adequate knowledge about causes, symptoms, and prevention. Cultural norms, poverty, and gender inequality were identified as major barriers to women’s sexual health awareness. Few respondents had sought medical consultation. The study calls for targeted education programs to improve awareness and promote reproductive health.